The effect of preventive exercises on the range of spine motion for squash players under 20 years old - Essam, Farah; Shaboot, Ali (Journal of Physical Education, 2023)
The research aimed to identify the values of the range of spine motion and to identify the significance of the differences between the pre- and post-tests for squash players under 20 years old. The Research subject were (12) person of squash player. Special tests were conducted on them in squash courts at the College of Physical Education and Sports Sciences-University of Baghdad. Aafter analyzing and discussing the results, the researchers concluded that there are significant differences between the pre and posttests because of the preventive exercises which prepared for this purpose. The researchers recommend conducting extensive studies for this game and paying attention to the preventive aspect of the players in order to avoid their exposure to lower back injuries, which is one of the most common injuries in this game.